Analisis Kinerja Gapoktan Setia dalam Pengelolaan Hutan Kemasyarakatan (Studi Kasus Hutan Kemasyarakatan Desa Oelekam, Kecamatan Mollo Tengah, Kabupaten Timor Tengah Selatan) - Erivaldi Dangu Uba; Ludji Michael Riwu Kaho; Astin E. Mau; Roni Haposan Sipayung (Wana Lestari, 2026)
Community forestry is one of the government's efforts in protecting forests by involving the community in their management. Oelekam village is one of the villages that received IUPHKm. Institutional in the management of HKm is an aspect that is very influential on the success or failure of HKm. This study aims to determine the institutional performance of Gapoktan Setia and the impact of HKm. Institutional performance data was obtained by interviews and questionnaire assistance, while vegetation composition data was obtained by vegetation analysis using the transect method. Processing of institutional performance data using Likert scale. The existence of IUPHKm has had a good impact on vegetation composition with an increase in tree composition in the 2015-2021 period, but there is still a need for improvements in the institutional sector so that HKm has a significant impact on communities and forests. The results showed that the institution of the loyal Association has not run well, as evidenced by the indicators of rights, responsibility, revenue and relationships which are considered to have received low scores. Based on Likert scale analysis, the rights indicator from the loyal association obtained a score of 2.04 (less good, the responsibility indicator obtained a score of 2.04 (less good), the result indicator obtained a score of 2.13 (less good), the result indicator obtained a score of 2.12 (less good). The absence of distribution of work areas for each member, lack of awareness of members, lack of deliberation, age dominated by old productive age and low education as well as inadequate infrastructure and infrastructure are factors that cause the slow institutional growth of the Setia association. The results of vegetation analysis show that there are plant species that have the potential to be developed such as tamarind (Tamarindus indica), candlenut (Aleurites moluccana), avocado (Persea americana) and johar (Senna siamea).